2014
DOI: 10.18700/jnc.2014.7.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity by Cefepime: Case-Control Study

Abstract: Background: Cefepime is a fourth-generation cephalosporin widely used for empiric treatment of severe infections. Neurotoxicity by cefepime have been reported due to γ-aminobutyric acid A receptor inhibition or other mechanisms. The aim of this study was to evaluate the risk factors for cefepime-induced neurotoxicity between group showing cefepime-induced neurotoxicity and group without neurotoxicity. Methods: From Jan 2005 to June 2010, a total of 2,461 patients (older than 20) who used cefepime were consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Incidence in critically ill patients [6] and in patients with hematologic malignancies [24] was 15% and 4.1%. The incidence of CIN in a retrospective case-control study in Korean patients was 0.85% [25]. The incidence in ESRD patients was 7.5%, but was 22.2% in ESRD patients with preexisting CNS morbidity [17].…”
Section: Incidencementioning
confidence: 97%
“…Incidence in critically ill patients [6] and in patients with hematologic malignancies [24] was 15% and 4.1%. The incidence of CIN in a retrospective case-control study in Korean patients was 0.85% [25]. The incidence in ESRD patients was 7.5%, but was 22.2% in ESRD patients with preexisting CNS morbidity [17].…”
Section: Incidencementioning
confidence: 97%
“…This study found that decreased eGFR was the most-significant risk factor for CIE. We showed that lower eGFR levels and dialysis were related to a higher incidence of CIE. We further found that 63.6% of the CIE patients had an eGFR of below 60 mL/min/1.73 mm 2 , which is similar to previous studies. 8 Among patients with reduced renal function who do not receive dialysis, the incidence of CIE was highest when eGFR was above 11 mL/min/1.73 mm 2 and below 30 mL/min/1.73 mm 2 . Further studies are needed to explain whether the physician had followed the dosing standard according to the eGFR of each patient, and what the serum level of cefepime was for each patient.…”
Section: Jcnmentioning
confidence: 98%
“…Fugate et al 9 found that 7 of 100 patients in an intensive care unit (ICU) setting had definite CIE. In Korea, Kang and Kim 8 reported that 21 (0.85%) of 2,461 patients were diagnosed with CIE. This wide range of the reported incidence rates may be expected given both the heterogeneity in diagnostic criteria for CIE and the diversity of the populations analyzed in these studies.…”
Section: Jcnmentioning
confidence: 99%
See 2 more Smart Citations